Engaging the lysosomal compartment to combat B cell malignancies - Grønbæk, Kirsten (American Society for Clinical Investigation, 2009)
The combination of rituximab, a type I anti-CD20 mAb, with conventional chemotherapy has significantly improved the outcome of patients with B cell malignancies. Regardless of this success, many patients still relapse with therapy-resistant disease, highlighting the need for the development of mAbs with higher capacity to induce programmed cell death. The so-called type II anti-CD20 mAbs (e.g., tositumomab) that trigger caspase-independent B cell lymphoma cell death in vitro and show superior efficacy as compared with rituximab in eradicating target cells in mouse models are emerging as the next generation of therapeutic anti-CD20 mAbs. In this issue of the JCI, Ivanov and colleagues identify the lysosomal compartment as a target for type II mAbs (see the related article beginning on page 2143). These data encourage the further clinical development of type II mAbs as well as other lysosome-targeting drugs in the treatment of B cell malignancies.